2019
DOI: 10.1007/s00438-019-01617-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationship and genetic history of Central Asian Kazakhs inferred from Y-chromosome and autosomal variations

Abstract: The Xinjiang Uyghur Autonomous Region of China (XUARC) with 47 ethnic groups is a most colourful ethnic region of China, harboring abundant genetic and cultural diversity, which harbors 47 ethnic groups. The Kazakhs are the third largest ethnic group (7.02%) after Uyghur (46.42%) and Han (38.99%) in Xinjiang, but their genetic diversity and forensic characterization are poorly understood. In the current study, we genotyped 15 autosomal short tandem repeat (STR) loci and 10 Y-STRs on 889 individuals (659 male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…For the Afghan Hazara population, the Afghan population (0.0009) from Afghanistan showed the closest genetic distance and for the Pakistani Hazara group, the Afghan population (0.0381) from Afghanistan showed the closest genetic distance To investigate the paternal relationship among these three and other reference populations, we have generated the MDS plot (figure 1) based on pairwise Rst matrix from supplementary table 3. In the MDS plot, we have seen that the Hazara population from Afghanistan is located closer to the Afghan population from Afghanistan and the Pathan population from northern Afghanistan which is similar to the results of another study 32 , while Pakistani Hazara lined closer to Kazakh and Mongolian population which is similar to our previous study’s results 27,33 .…”
Section: Resultssupporting
confidence: 90%
“…For the Afghan Hazara population, the Afghan population (0.0009) from Afghanistan showed the closest genetic distance and for the Pakistani Hazara group, the Afghan population (0.0381) from Afghanistan showed the closest genetic distance To investigate the paternal relationship among these three and other reference populations, we have generated the MDS plot (figure 1) based on pairwise Rst matrix from supplementary table 3. In the MDS plot, we have seen that the Hazara population from Afghanistan is located closer to the Afghan population from Afghanistan and the Pathan population from northern Afghanistan which is similar to the results of another study 32 , while Pakistani Hazara lined closer to Kazakh and Mongolian population which is similar to our previous study’s results 27,33 .…”
Section: Resultssupporting
confidence: 90%
“…Fst is a standardized variance of haplotype frequency and assumes genetic drift as being the agent that differentiates pairwise Rst matrix from supplementary table 3. In the MDS plot, we have seen that the Hazara population from Afghanistan is located closer to the Afghan population from Afghanistan and the Pathan population from northern Afghanistan which is similar to the results of another study 32 , while Pakistani Hazara lined closer to Kazakh and Mongolian population which is similar to our previous study's results 27,33 .…”
Section: 2phylogenetic Analyses and Population Comparisonssupporting
confidence: 90%
“…These types of features are usually inferred as past male-lineage expansions 35 . Star-like features of haplotypes comprising haplogroup M217 (C2) have been reported previously in Hazara, Mongol, and Kazakh populations 27,33,36 . An explanation about its origin in Mongolia was about ∼1,000 years ago 36 .…”
Section: Inference Of Ancestry Based On Y Strssupporting
confidence: 69%
“…Many previous studies have suggested extensive genetic admixture between East and West Eurasians in northwest China (Ning et al, 2019; Wang et al, 2019, 2021; Adnan et al, 2020, 2021; Wen et al, 2020; Zhao et al, 2020; He et al, 2021; Ma et al, 2021; Yang et al, 2021; Yao et al, 2021; Zhang et al, 2021), but a few focus on Tajiks. A 2018 paper by Min‐Sheng Peng et al used mitochondrial genome analysis to understand the maternal origin of multiple ethnic groups on the Pamir Plateau.…”
Section: Introductionmentioning
confidence: 99%